Design of a business sustainability measurement method for based on neutroalgebras generated by the combining function in prospector and neutrosophic 2-tuple linguistic models - Alvarez-Bernuy, Silvia Marina (2024)
Business sustainability has become a global imperative in response to the environmental, social, and economic challenges facing our world. In this context, the measurement and evaluation of business sustainability have become crucial to guide the actions of organizations towards more responsible and sustainable practices. However, the lack of specific measurement instruments for specific regional contexts may limit the ability of companies to evaluate and improve their sustainability performance. In this paper, we present the design of a business sustainability measurement method adapted to the context of Tarma, Peru. Tarma, a region located in the heart of the Peruvian Andes, is characterized by its cultural, environmental, and economic diversity, making it a unique context to address business sustainability. This article proposes a method for measuring business sustainability based on the Neutrosophic 2-tuple Linguistic Model, which includes an aggregation operation based on a NeutroAlgebra generated by Combining Functions in Prospector.